ANALISIS FAKTOR KESESUAIAN PENEMPATAN KERJA DAN KOMPETENSI TERHADAP KINERJA PERSONAL PADA DIREKTORAT RESERSE KRIMINAL KHUSUS (DITRESKRIMSUS) POLDA LAMPUNG - Ari Efra Hanisa; Iskandar Ali Alam (PT Saha Kreasi Indonesia, 2026)
This study aims to analyze the influence of job placement suitability and competency on personnel performance at the Directorate of Special Criminal Investigation (Ditreskrimsus) of the Lampung Regional Police. The study is motivated by the suboptimal performance of personnel, as reflected in the failure to achieve case resolution targets and the existence of job placements that are not fully aligned with personnel competencies, which are presumed to affect the effectiveness of task execution and organizational performance. This research employed a quantitative approach with an associative research design. The population consisted of all 197 personnel of the Directorate of Special Criminal Investigation, with a sample of 66 respondents determined using the Slovin formula. Data were collected through questionnaires, documentation, and literature review, and analyzed using IBM SPSS Statistics version 25 through descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The study is expected to provide empirical evidence regarding the influence of job placement suitability and competency on personnel performance, both partially and simultaneously. The findings are expected to serve as a reference for the Directorate of Special Criminal Investigation of the Lampung Regional Police in optimizing competency-based personnel placement policies, improving the quality of human resources, and enhancing sustainable organizational performance.